Biochemical characterization of rat sperm acrosomal hyaluronidase - Herbosa, Gloria
Hyaluronidase from rat cauda epidfdymal sperm was extracted by the non-ionic detergent, Triton X-100. I had optimum activity at pH 4.0 and at 37oC. The unstable nature of the enzyme during storage was observed. Hyaluronidase from rat sperm was partially purified using a number of single step purification techniques--- DEAE-cellulose chromatography, cellulose phosphate chromatography, Sephadex G-100 chromatography and Sepharose 4B chromatography. Cellulose phosphate column chromatography produced the most significant purification with the partially purified preparation showing 232 turbidity reducing units per mg protein. Disc gel electrophoresis showed one major component with a minor band of faster mobility. The inactivation of the enzyme possibly because of dissociation into smaller aggregates as a results of storage, lyophilization and interaction with polydextran or agarose gel as observed in disc gel electrophoretic patterns is discussed. Km of hyaluronidase with hyaluronic acid as substrate was 0.40 mg per ml and V max was 15.9 mg hyaluronic acid digested per min per mg protein by the Lineweaver-Burk plot. Fe+3 and Cu+2 significantly inhibited the enzyme activity at a concentration of 0.0075 M both in the crude acrosomal extracts and in the partially purified preparation. Chondroitin sulfates A and B and heparin were effective competitive inhibitord of hyaluronidase. Higher concentrations (0.32 mg per ml) of these substrate analogs were required to effectively inhibit activity in the partially purified preparation than in crude acrosomal extracts. Significance of the results of in vitro inhibition in future in vivo studies is presented.